CYP1B1 Gene Mutations Causing Primary Congenital Glaucoma in Tunisia. (July 2014) - Bouyacoub, Yosra; Ben Yahia, Salim; Abroug, Nesrine; Kahloun, Rim; Kefi, Rym; Khairallah, Moncef; Abdelhak, Sonia
Summary Primary congenital glaucoma (PCG) is responsible for a significant proportion of childhood blindness in Tunisia. Early prevention based on genetic diagnosis is therefore required. This study sought to determine the frequency of CYP1B1 (cytochrome P450, family 1, subfamily B, polypeptide 1) mutations in 18 PCG patients, recruited from Central and Southern of Tunisia. Genomic DNA was extracted and the coding regions of CYP1B1 were analysed by direct sequencing. A phylogenetic network of CYP1B1 haplotypes was drawn using the median‐joining algorithm. Sequence analysis revealed a "tetra‐allelic mutation" (two novel mutations, p.F231I and p.P437A in the homozygous state) in one patient. The healthy members of his family carried those variations on the same allele. Two previously described mutations p.G61E and c.535delG were also identified in the homozygous state in seven and two probands, respectively. Seven single‐nucleotide polymorphisms were identified and used to generate haplotypes. Our results showed that the CYP1B1 mutations were present in 55% of Tunisian PCG patients' alleles. Haplotype analysis allowed us to define the proto‐haplotype and to confirm historical migratory flows. Establishment of PCG genetic aetiology in Tunisia will improve genetic diagnosis and counselling.